2021
DOI: 10.26552/com.c.2021.3.a137-a149
|View full text |Cite
|
Sign up to set email alerts
|

Electrification of Public Transport Bus Fleet: Identification of Business and Financing Models

Abstract: The paper presents possible models of electric buses purchase financing, taking into account purchase prices higher now than in the case of traditional buses. During the research, the solutions used on several continents and in many countries were analysed, including the USA, China and many European countries. The qualitative research methods were used, focusing less on the describing and dimensioning the current state and more on creating and presenting theories and the implementation proposals themselves. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…In the case of DBs, the volume of pollutant emissions was very much correlated with the level of diesel consumption (which had a different criterion for bid selection). Similar conclusions have been reached in other studies [64,82], as authors found that "external costs are not entirely or only to a small extent taken into account as evaluation criteria in the bidding procedures for vehicle purchases".…”
Section: Do the Criteria Used In Tendering For Electric Buses Differ ...supporting
confidence: 90%
“…In the case of DBs, the volume of pollutant emissions was very much correlated with the level of diesel consumption (which had a different criterion for bid selection). Similar conclusions have been reached in other studies [64,82], as authors found that "external costs are not entirely or only to a small extent taken into account as evaluation criteria in the bidding procedures for vehicle purchases".…”
Section: Do the Criteria Used In Tendering For Electric Buses Differ ...supporting
confidence: 90%
“…Finally, the decarbonization process of the transport sector is and should be carried out using biofuels, synthetic fuels, and electricity. However, it will be difficult to implement, by 2050, the total electrification of the transport sector, especially if the associated costs do not drop drastically, either in terms of vehicle acquisition or in terms of installation and access to electric vehicle charging, as well as the price of electricity [99,100]. The total replacement of a national fleet implies a high financial investment and political measures to scrap vehicles, with significant impacts on the environment.…”
Section: Electrification Of the Economymentioning
confidence: 99%